Sistem Pembayara SPP Siswa Berbasis Web Pada SMK AL-IKHLAS LEGOK - surya, risky adi (Jurnal Kreativitas Mahasiswa Informatika, 2021)
SPP payment still often experience problems such as data collection and recording of payments made so far which are used are still simple, still using books as a means of recording tuition payments. Therefore, there are often problems in making reports for students in making tuition payments that are needed precisely and accurately so that they have not been able to produce the required web-based tuition payment system. In the current technological era, it is necessary to innovate the use of technology in the world of education to assist school financial administration so that data collection and payment processes run effectively and efficiently. In this journal, we will discuss the web-based tuition payment system. The research method used is the Prototype Method which allows interaction between system developers and system users, so as to overcome incompatibility between developers and users. With this application, the school can use it in making payments to make it easier and more efficient, and can make it easier to make tuition reports. Keywords : SPP payment, system, web